Železobetonové protipovodňové stěny - Roudný, Tomáš (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Práce se zabývá návrhem dvou variant železobetonových monolitických protipovodňových stěn. Řešení obsahuje návrh a posouzení stěn dle ČSN EN 1992 na 1. mezní stav únosnosti a 2. mezní stav použitelnosti s ohledem na omezení šířky trhlin.

The work deals with design of two variants of reinforced concrete walls for line flood-protection precautions. The solution include design and assessment of walls according to ČSN EN 1992 in the ultimate limit state and the serviceability limit state (crack limitation).
REINFORCED CONCRETE WALLS FOR THE LINE FLOOD-PROTECTION PRECAUTIONS
Keywords: Železobeton; podzemní stěny; protipovodňová stěna; zatížení; podloží; zemní tlaky; omezení trhlin; GEO5.; Reinforced concrete; diaphragm wall; wall for the line flood protection precautions; load; soil base; earth pressures; crack limitation; GEO5.